2020
DOI: 10.1111/ijpo.12728
|View full text |Cite
|
Sign up to set email alerts
|

High intake of added sugars is linked to rapid weight gain in infancy, breastfeeding ≥12 months may protect against this: A preliminary investigation

Abstract: Summary Background Consumption of added sugars is linked to excess adiposity in older age groups and breastfeeding has been shown to protect against later obesity. Objectives This investigation aimed to determine whether intake of added sugars associates with rapid weight gain in individuals under 2 years of age, if intake of added sugars associates with breastfeeding duration, and how both influence body weight. Methods A cross‐sectional analysis of data from three 24‐hours dietary recalls collected from 141 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…This is a cross-sectional analysis of baseline data from 101 mother-infant/toddler dyads (infant/toddler aged 9 to <16 months) participating in a longitudinal randomized controlled trial [ 1 ]. Exclusion criteria included: infants born preterm (<37 weeks gestation), low-birth weight infants (<2500 g), infants/toddlers with known medical problems, infants/toddlers consuming special diets, infants/toddlers with developmental delays or disabilities, maternal smoking, alcohol abuse, or controlled substance use during pregnancy, mother <18 years of age, high risk pregnancy (Gestational Diabetes Mellitus, pre-eclampsia, etc.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a cross-sectional analysis of baseline data from 101 mother-infant/toddler dyads (infant/toddler aged 9 to <16 months) participating in a longitudinal randomized controlled trial [ 1 ]. Exclusion criteria included: infants born preterm (<37 weeks gestation), low-birth weight infants (<2500 g), infants/toddlers with known medical problems, infants/toddlers consuming special diets, infants/toddlers with developmental delays or disabilities, maternal smoking, alcohol abuse, or controlled substance use during pregnancy, mother <18 years of age, high risk pregnancy (Gestational Diabetes Mellitus, pre-eclampsia, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included: infants born preterm (<37 weeks gestation), low-birth weight infants (<2500 g), infants/toddlers with known medical problems, infants/toddlers consuming special diets, infants/toddlers with developmental delays or disabilities, maternal smoking, alcohol abuse, or controlled substance use during pregnancy, mother <18 years of age, high risk pregnancy (Gestational Diabetes Mellitus, pre-eclampsia, etc. ), or multiple gestation [ 1 ]. Three participants who consumed calories estimated to be ±2 SD from their estimated energy requirement (Institute of Medicine’s Food and Nutrition Board [ 25 ]) were not included in the present analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been described that a high intake of added sugars in individuals below age 2 associates with rapid weight gain, though breastfeeding ≥12 months appears protective against this (Kong et al 2021). A study from the US found that markers of lower socioeconomic status were strongly associated with earlier juice introduction, which, in turn, relates to sugary beverage intake in childhood, potentially replacing water (Robinson et al 2021).…”
Section: Introductionmentioning
confidence: 99%